Application to detect toxicity of recycled plastics using boar spermatozoa motility - Aalto, Milja (2024)
Plastic as waste decomposes slowly and the quantities are large. Therefore, plastic recycling is essential. However, a key problem with recycled plastic and plastic products is their additives, such as plastic softeners and inhibitors for mold and bacteria, which contain chemicals that may be toxic to mammalian cells. Harmful additives are difficult to avoid as the manufacturer is not obliged to inform about them. Therefore, in recycled plastic mixtures, their exact content and toxicity, is not known. The aim of this study was to apply an assay method to measure changes in boar spermatozoa motility using the automated sperm analysis program (ISAS v1) with a particular focus on recycled plastic. The applied assay method did not give particularly accurate results. The inaccuracy of the results was affected e.g. by a large natural variability, deviation between replicate samples, and the computer program which did not calculate motility completely reliably. Despite the use of the ISAS program, the person doing the work also had to use subjective selection. The assay method works most reliably when there is a substantial change in spermatozoa motility within three days due to the chemical, and the semen is of good quality, in which case the negative control motility reduces only slightly. As part of application process, a case study was carried out, where spermatozoa motility measurements were conducted after exposure to two types of recycled plastic, a grocery store's plastic bag (90% was recycled plastic) and for Barbie doll’s leg (from the 70s). In the tests, the negative control was the semen as it came from the artificial insemination station, and in the positive control chemical triclosan was used, which is an antibacterial agent used also in plastics. With this assay method and equipment and using 2 µg/ml triclosan, 50% of rapid movement of boar spermatozoa motility was lost between 1 and 3 days of exposure. The assay method gave indicative results that the plastic bag and Barbie contain substances toxic to boar spermatozoa. Rapid movement of boar spermatozoa decreased 53% when exposed to a piece of plastic bag (2x3 cm) and 60% when exposed to pieces of Barbie’s leg (2 pieces of 0,5x2 cm) for three days. Overall, the case study demonstrated that presented assay method can be used to study the toxicity of recycled plastics.